Fruiting Body of Niuchangchih (Antrodia camphorata) Protects Livers against Chronic Alcohol Consumption Damage - Huang, Chia-Hsin; Chang, Yuan-Yen; Liu, Cheng-Wei; Kang, Wen-Yu; Lin, Yi-Ling; Chang, Hsien-Chang; Chen, Yi-Chen (Journal of agricultural and food chemistry, 2010)
An alcoholic fatty liver disease was induced by drinking water containing 20% (w/w) alcohol. Therapeutic groups were orally administrated dosages of 0.25 g silymarin/kg body weight (BW) and a low dosage of Niuchangchih (Antrodia camphorata) (0.025 g/kg BW) and a high dosage of Niuchangchih (0.1 g/kg BW) per day. Niuchangchih, especially at the high dosage, not only showed a hypercholesterolemic effect (p < 0.05) but also reduced (p < 0.05) hepatic lipids in alcohol-fed rats. Those beneficial effects could be partially attributed to higher (p < 0.05) fecal cholesterol and bile acid outputs, as well as downregulations (p < 0.05) of 3-hydroxy-3-methylglutaryl-CoA reductase, sterol regulatory element-binding protein-1c, acetyl-CoA carboxylase, fatty acid synthase, and malic enzyme gene expressions; meanwhile, there was an upregulation of low-density lipoprotein receptor and peroxisome proliferator-activated α gene expression. Besides, Niuchangchih also enhanced (p < 0.05) the liver glutathione, Trolox equivalent antioxidant capacity, and activities of superoxide dismutase, catalase, and glutathione peroxidase and decreased the liver malondialdehyde content, which also partially contributed to the lowered (p < 0.05) serum aspartate aminotransferase levels and no observed lesion in the histological examination of alcohol-fed rats.